Last seen alive [videorecording (DVD)] - Butler, Gerard, 1969-; Alexander, Jaimie; Hornsby, Russell; Embry, Ethan, 1978-; Irby, Michael; Hogan, Cindy; Altman, Bruce (Vertical Entertainment, 2022)
When Will's estranged wife Lisa disappears during a stop at a gas station, Will must embark on a frantic undertaking to rescue her while eluding the police who suspect him of foul play.